Analiza regulacji dotyczących wykorzystania narzędzi sztucznej inteligencji w pracach dyplomowych - Pinkalski, Zbigniew (PRAWO i WIĘŹ, 2025)
This paper discusses the use of artificial intelligence (AI) systems in academic dissertations. Interest in this topic is growing, particularly as access to AI tools has become more widespread. The paper highlights that copyright law does not provide clear guidance on the limits of permissibility of the use of AI tools in dissertations. Therefore, the provisions of other laws have been analysed in this context. The paper also emphasises the role of internal guidelines of universities, which provide the most concrete answer to the question of the limits of the admissibility of the use of IS in diploma theses. The conclusions of the analysis point to the need for clear, nationwide guidelines for the use of AI tools in higher education.